Policies and interventions to reduce harmful gambling: an international Delphi consensus and implementation rating study. (August 2022) - Regan, Marguerite; Smolar, Maria; Burton, Robyn; Clarke, Zoe; Sharpe, Casey; Henn, Clive; Marsden, John
Summary: There is increasing public health concern about harmful gambling, but no consensus on effective policies and interventions to reduce risk and prevent harm has been reached. Focusing on policies and interventions (ie, measures), the aim of this study was to determine if expert consensus could be reached on measures perceived to be effective that could be implemented successfully. Our work involved a pre-registered, three-round, independent Delphi panel consensus study and an implementation rating exercise. A starting set of 103 universal and targeted measures, which were sourced from several key resources and inputs from public health stakeholders, were grouped into seven domains: price and taxation; availability; accessibility; marketing, advertising, promotion, and sponsorship; environment and technology; information and education; and treatment and support. Across three rounds, an independent panel of 35 experts individually completed online questionnaires to rank each measure for known or potential effectiveness. A consensus was reached if at least 70% of the panel judged a measure to be either not effective, moderately effective, or highly effective. Then, each measure that reached a consensus for effectiveness was evaluated on four implementation dimensions: practicability, affordability, side-effects, and equity. A summative threshold criterion was used to select a final optimal set of measures for England. The panel reached consensus on 83 (81%) of 103 measures. Two measures were judged as ineffective by the panel. The remaining 81 effective measures were drawn from all domains (14 of 15 measures in the the marketing, advertising, promotion, and sponsorship domain were judged as effective, whereas five of ten measures in the information and education domain were judged as effective). During the evaluation exercise, the 81 measures were assessed for likelihood of implementation success. This assessment considered the practicality, affordability, ability to generate unanticipated side-effects, and ability to decrease differences between advantaged and disadvantaged groups in society of each measure. We identified 40 universal and targeted measures to tackle harmful gambling (three measures from the price and taxation domain; ten from the availability domain; five from the accessibility domain; six from the marketing, advertising, promotion, and sponsorship domain; eight from the environment and technology domain; three from the information and education domain; and five from the treatment and support domain). Implementation of these measures in England could substantially strengthen regulatory controls while providing new resources. The findings of our work offer a blueprint for a public health approach to preventing harms related to gambling.